2019
DOI: 10.1111/ijal.12256
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic complexity across proficiency and languages: L2 and L1 writing in Dutch, Italian and Spanish

Abstract: This study explores to what extent syntactic complexity as assessed by four types of complexity measures may vary in written, argumentative texts of L2 learners (A2‐B1) and native writers of Dutch, Italian and Spanish. All texts were assessed by calculating both overall complexity measures and more fine‐grained measures that focus on the type and number of coordinate and subordinate structures, and the use of post‐modifiers within the NP. The results of the study indicate that there is variation in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 38 publications
2
10
0
3
Order By: Relevance
“…Hitherto, measures of morphology may generally have been neglected due to the large number of studies done on L2 English and English being a morphologically poor language where those measures are less informative. The current result confirms the need to take into account cross‐linguistic variation (De Clercq, ; Bernardini & Granfeldt, ; Kuiken & Vedder, ) and to establish reliable measures of morphological complexity (Pallotti, ).…”
Section: Discussionsupporting
confidence: 82%
“…Hitherto, measures of morphology may generally have been neglected due to the large number of studies done on L2 English and English being a morphologically poor language where those measures are less informative. The current result confirms the need to take into account cross‐linguistic variation (De Clercq, ; Bernardini & Granfeldt, ; Kuiken & Vedder, ) and to establish reliable measures of morphological complexity (Pallotti, ).…”
Section: Discussionsupporting
confidence: 82%
“…For example, as Ortega (2015) stated, L1 is "a moderating variable of L2 syntactic complexity" (p. 84). This was also proved in Lu and Ai's (2015), Jiang, Bi, and Liu's (2019), Kuiken and Vedder's (2019), Khushik and Huhta's (2020) as well as Ströbel, Kerz, and Wiechmann (2020) studies. Further, genre/task/content also play roles in syntactic complexity in writing and L2 proficiency is also "a powerful source of influence that modulates syntactic complexity" (Ortega 2015, p. 88).…”
Section: Introductionsupporting
confidence: 57%
“…It is found that they tend to use combine two or more coordinate clause to make a long sentence. Other researchers also confirmed that the L2 learners used coordinate phrases in their L2 writings as frequent as their L1 writings (Kuiken & Vedder, 2019). That is why their mean length of clause are similar since they construct it from similar structure that is coordinate phrases.…”
Section: Discussionmentioning
confidence: 75%